2020
DOI: 10.3390/microorganisms8060813
|View full text |Cite
|
Sign up to set email alerts
|

Influence of High Hydrostatic Pressure on the Identification of Lactobacillus by MALDI-TOF MS- Preliminary Study

Abstract: In the present study, we assessed the ability of MALDI-TOF MS (matrix-assisted laser desorption ionization time-of-flight mass spectrometry) to identify microbial strains subjected to high hydrostatic pressure (HHP) as a stress factor. Protein changes induced by HHP can affect the identification of microorganisms when the identification technique is based on the protein profile. We evaluated two methods, namely MALDI-TOF MS and 16S rDNA sequencing, as a valuable tool to identify Lactobacillus species isolated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 21 publications
1
18
0
2
Order By: Relevance
“…In the strain, L. paracollinoides KKP 3567, the expression levels for the dnaK and ctsR were below the detection limit, but a slight increase of the expression hrcA after HHP treatment was noticed. The impact of HHP on proteome was previously described in Bucka-Kolendo et al [17]. Overall, the analysis of the viability showed that the pressurization did affect the studied strains, and the level of survival has decreased compared to the control.…”
Section: Hrca Genesupporting
confidence: 52%
See 2 more Smart Citations
“…In the strain, L. paracollinoides KKP 3567, the expression levels for the dnaK and ctsR were below the detection limit, but a slight increase of the expression hrcA after HHP treatment was noticed. The impact of HHP on proteome was previously described in Bucka-Kolendo et al [17]. Overall, the analysis of the viability showed that the pressurization did affect the studied strains, and the level of survival has decreased compared to the control.…”
Section: Hrca Genesupporting
confidence: 52%
“…The 15 strains of LAB were isolated from food (juices, beverages, and beers) samples obtained commercially, to determine the source of microbial contamination of the products. The strains selected for examination were characterized by phenotypical and phylogenetical characteristics to confirm their identification, as described in Bucka-Kolendo et al [17]. LAB strains used in the studies as well as the introduced new nomenclature proposed by Zheng et al [18] are presented in Table 1.…”
Section: Lab Strains and Culture Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the MALDI-TOF technique allowed better identification of bacterial strains in the tested food products (92% correct identification), compared to the qPCR method (Angelakis et al, 2011). However, some studies showed (Bucka-Kolendo et al, 2020) that treating lactic acid bacteria with stress factor, like high hydrostatic pressure (HHP), can affect the identification of microorganisms, if the identification technique is based on the protein profile. The data obtained from the protein mass fingerprinting analysis of some lactobacilli strains showed differences in unpressured and pressured mass spectrum profiles (MSPs), which influenced the results of the identification.…”
Section: Identification and Typing Of Microorganisms Isolated From Foodmentioning
confidence: 99%
“…Food processing can involve high-hydrostatic pressure treatments to inactivate foodborne pathogens or spoilage microorganisms. However, this non-thermal pasteurization method can modify the protein profile of bacteria, leading then to misidentification with the rapid MALDI-TOF MS (matrix-assisted laser desorption ionization time-of-flight mass spectrometry) method [ 10 ].…”
mentioning
confidence: 99%